Human Papillomavirus Infection and Awareness of Human Pappillomavirus Vaccines among Various Ethnicities in Libya - Salma Korbag; Issa Korbag (Faculty of Medicine Universitas Padjadjaran, 2021)
Background: Human papillomavirus (HPV) plays a role in increasing the risk of cervical cancer and other cancers. This study aimed to explore the incidence of HPV infection among various ethnicities in Libya. Furthermore, awareness and knowledge of HPV vaccines in the community were explored.Methods: A descriptive study was conducted to present HPV infection among cancer cases using the National Cancer Registry of Libya year 2011-2020, including gender, skin color, and ethnicity. Furthermore, awareness and knowledge of the HPV vaccines were assessed using questionnaires distributed through social media. Data were presented in percentage.Results: In total, there were 33,526 (58.1%) infected HPV-related cancers out of 57,620 cancer cases, of whom 25,296 (75.4%) were women and 8,230 (24.6%) were men. Based on cancer sites, the incidence of HPV-related cancers among whites was higher (>63% and more) than blacks except for anal cancer, of which blacks had a slightly higher incidence (54%) in females and 57% in males). Based on ethnicity, native Libyans such as Tabu, Touareg, and Berbers had different cancer sites. Moreover, the knowledge and awareness about HPV and related cancers were very poor among the population in Libya.Conclusions: Although HPV cancers represent a high percentage of cancer burdens among Libyans, awareness and knowledge on HPV and related cancer are lacking. Better education and provision of the HPV vaccines for future generations may eliminate and reduce HPV-related cancers.